Further supporting SMARCC2‐related neurodevelopmental disorder through exome analysis and reanalysis in two patients - Li, Dong; Downes, Helen; Hou, Cuiping; Hakonarson, Hakon; Zackai, Elaine H.; Schrier Vergano, Samantha A.; Bhoj, Elizabeth J. (American journal of medical genetics. Part A, 2022)
BAFopathies are a heterogenous group of neurodevelopmental disorders caused by mutations in genes encoding subunits of the BAF complex, and they exhibit a broad clinical phenotypic spectrum. Pathogenic heterozygous variants in SMARCC2 have been implicated in Coffin–Siris syndrome 8 (MIM 618362) with variable neurodevelopmental presentations. We report here two relatively severely affected patients with two different SMARCC2 variants: one has de novo pathogenic variant, c.1824_1826del, p.(Leu609del), in a suspected hotspot region through reanalysis of previously negative clinical exome data, and the other has a likely pathogenic loss‐of‐function variant, c.1094_1097delAGAA, p.(Lys365Thrfs*12) through exome analysis in an adopted subject. Regardless of variant type, both patients have severe developmental delays, severe speech delay, short stature, hypotonia, seizures, and craniofacial dysmorphisms, blurring previously speculated genotype–phenotype correlation on missense and loss‐of‐function variants. This report extends our understanding of the genotypic and phenotypic spectrums of the SMARCC2‐related neurodevelopmental disorder.